Model Continuing Professional Development (CPD) Pada Sekolah Luar Biasa (SLB) Negeri Garut Kota - Reva Tanti Nurbaeti; Deddy Mulyadi; Arundina Dijah Retno Pratiwi (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2021)
Teachers as educators at SLBN Garut City, who have a duty to provide instruction to students, have a very big responsibility in carrying out their role as educators in schools. The problems in handling children with special needs at school are very complex, starting from children, parents to school, even need extra handling. The occurrence of psychological conflicts between parents and the presence of their children, their own condition, the community environment and the readiness of schools to educate children with special needs. Also the most important thing is the condition of the teacher who provides learning to students, which is seen from the aspect of his competence as an educator who handles children with special needs. Continuous Professional Development is a process of action taken by teachers on an ongoing basis in order to improve their competence to support their career as a professional teacher. The focus of the CPD goals of teachers tends to lie in improving and enhancing the quality of learning carried out by teachers. In order to achieve quality learning objectives, increasing the competence and professionalism of teachers is a must in pedagogical aspects, etc. Teacher competence needs to be improved programmatically, continuously through various systems of professional development, so as to increase the ability of these teachers. Competencies ranging from pedagogic, personality, social, and professional must receive important attention. Constraints faced in competency development range from skills in the aspects of learning, mastery of ICT, and busy teaching schedules to aspects of teacher competency problems at SLBN Garut City. Efforts are to continue to always perform competency enhancement program, which is also more emphasis on the development of a model that has the aspect of sustainability models or Continuing Professional Development (CPD).